Mating system and reproductive success of Cuitlauzina pendula La Llave & Lex (Orchidaceae) at the National Park ‘Barranca del Cupatitzio’ of Uruapan, Michoacán, México - Pérez Decelis, Verónica A. (Universidad de Costa Rica, 2013)
.